Analisis Cara Berpikir Siswa dalam Menyelesaikan Soal High Order Thinking Skills (HOTS) Kelas VIII MTs Pertiwi Kuningan - Juwita, Ii; Ricki Yuliardi, Ricki (Indo-MathEdu Intellectuals Journal, 2024)
Abstract. The results of the 2022 International Student Assessment (PISA) for Indonesia show a decrease of 12-13 points, but Indonesia's ranking has increased by 5-6 compared to 2018. So, Indonesia is ranked 69th, this shows that the competence of Indonesian children is still low in critical skills and solving abilities. problem with HOTS. The aim of this research is to determine students' thinking abilities in solving HOTS type questions. This research is descriptive qualitative research. The subjects in this research were students of class VIII MTs Pertiwi Kuningan. Data collection techniques in this research used interviews, observation and documentation and were analyzed using triangulation analysis techniques which consisted of three stages, namely: data reduction, data presentation and conclusion drawing. The research results show that students' cognitive abilities in solving HOTS questions at MTs Pertiwi Kuningan vary, with the majority of students being at a good to high level of ability. However, there are challenges that need to be overcome, such as a lack of practice on similar questions and accuracy in answering questions. With the right strategies, such as practicing practice and increasing accuracy, as well as intensive support from teachers, students' abilities in applying, analyzing and evaluating HOTS questions can be improved